'Djabooly-djabooly: why don't they swim?': the ebb and flow of water in the lives of Australian Aboriginal women. Issue 3 (27th May 2019) - Stronach, Megan; Adair, Daryl; Maxwell, Hazel
ABSTRACT: Aquatic activities have been pivotal to the lifestyle of Australian Indigenous peoples for millennia. That historical connection with rivers, streams and beaches is a largely untold story. This paper considers one aspect of the story: the significance swimming for Aboriginal women. Aquatic activities were, for many Aboriginal communities, crucial for food, movement and leisure. Even a cursory trawl through newspapers and memoirs provides observations about the prowess of Aboriginal women as swimmers. But this skill-set dissipated in the wake of territorial conflict, resulting in the displacement or erosion of Aboriginal communities in coastal areas. The paper then moves to the contemporary era, starting with an assumption that the passion for, swimming has been lost for Aboriginal women. Stories about female Indigenous swimmers, alongside the recollections of two mature-age women, present a story of limited opportunity, discrimination and challenges by way of access to water and safety therein.